A Systems Biology Approach for Investigating Significant Biomarkers and Drug Targets Common Among Patients with Gonorrhea, Chlamydia, and Prostate Cancer: A Pilot Study - Abdulla Al Noman; Md. Kobirul Islam; Tasmiah Feroz; Md. Monir Hossain; Md. Shahariar Kabir Shakil (Bioinformatics and Biology Insights, 2023)
Having a previous history of sexually transmitted diseases (STDs) such as gonorrhea and chlamydia increases the chance of developing prostate cancer, the second most frequent malignant cancer among men. However, the molecular functions that cause the development of prostate cancer in persons with gonorrhea and chlamydia are yet unknown. In this study, we studied RNA-seq gene expression profiles using computational biology methods to find out potential biomarkers that could help us in understanding the patho-biological mechanisms of gonorrhea, chlamydia, and prostate cancer. Using statistical methods on the Gene Expression Omnibus (GEO) data sets, it was found that a total of 22 distinct differentially expressed genes were shared among these 3 diseases of which 14 were up-regulated (PGRMC1, TSC22D1, SH3BGRL, NNT, CTSC, FRMD3, CCR2, FAM210B, VCL, PTGS1, SLFN11, SLC40A1, PROS1, and DSE) and the remaining 8 genes were down-regulated (PRNP, HINT3, MARCKSL1, TMED10, SH3KBP1, ENSA, DERL1, and KMT2B). Investigation on these 22 unique dysregulated genes using Gene Ontology, BioCarta, KEGG, and Reactome revealed multiple altered molecular pathways, including regulation of amyloid precursor protein catabolic process, ferroptosis, effects on gene expression of Homo sapiens PPAR pathway, and innate immune system R-HSA-168249. Four significant hub proteins namely VCL, SH3KBP1, PRNP, and PGRMC1 were revealed by protein-protein interaction network analysis. By analyzing gene-transcription factors and gene-miRNAs interactions, significant transcription factors (POU2F2, POU2F1, GATA6, and HIVEP1) and posttranscriptional regulator microRNAs (hsa-miR-7-5p) were also identified. Three potential therapeutic compounds namely INCB3284, CCX915, and MLN-1202 were found to interact with up-regulated protein C-C chemokine receptor type 2 (CCR2) in protein-drug interaction analysis. The proposed biomarkers and therapeutic potential molecules could be investigated for potential pharmacological targets and activity in the fight against in patients with gonorrhea, chlamydia, and prostate cancer.